Allelopathic Effect of Populus Nigra Bark on Zea Mays in Agroforestry Ecosystems (Global Journal of Science Frontier Research, 2016)
The study was designed to explore the allelopathic effect of Populus nigra bark on Zea mays under labourtary condition during 2014-2015. The allelopathic influence of aqueous extracts of P. nigra bark have determined on the germination, seedling growth, fresh weight and dry weight of Zea mays. ANOVA (RCBD) showed no significant effects of concentration and duration on germination between group as well as within group. On plumule length the significant effects of concentration (F=28.1457) was found within group while the effect of duration (F=2.4125) showed significant effects within group and between group i.e. concentration and duration, no significant was found. On plumule length significant effects of concentration was found within group (F=17.2154) and between group (F= 12.8457) while the effect of 48h duration showed significant effects within group (F=4.8654). On fresh weight significant effects of high concentration was found within group (F=37.3254) and between group (F=18.5241) while the effect of duration (F=4.6584) showed significant effects within group. On dry weight significant effects of concentration (F=27.5684) was found within group. The effect of duration (F=412.8457) showed significant effects within group while between the group (F=7.76352) significant effect was present. These findings indicate that P. nigra bark sown in fields which had leaf and stem litter of test plant will be adversely affected regarding germination, growth and ultimately resulting in lower yield
Keywords: concentration effect; duration effect; germination; seedling growth; fresh weight and dry weight